2021
DOI: 10.1016/j.jclepro.2020.123737
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective optimization model to plan city-scale water systems with economic and environmental objectives: A case study in santiago, Chile

Abstract: Climate Change and its effects in water scarcity has become an important challenge for cities with water management problems. These problems require an integral planning of the city, which can be supported by optimization. The main goal of the research is to provide a regional optimization model for water networks, including new treatment options. The model is formulated as a multi objective mixed integer programming problem, focused on environmental and economic impact of the network, minimizing water extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This paper is based on a previous one where the simplified smallscale problem is presented. 5 In that research, a multiobjective optimization model was developed, applying the elimination of nonlinearities as a simplification strategy. The point is whether this strategy is the best among the available.…”
Section: ■ Problem Structurementioning
confidence: 99%
See 3 more Smart Citations
“…This paper is based on a previous one where the simplified smallscale problem is presented. 5 In that research, a multiobjective optimization model was developed, applying the elimination of nonlinearities as a simplification strategy. The point is whether this strategy is the best among the available.…”
Section: ■ Problem Structurementioning
confidence: 99%
“…The model applied to this problem is based on the previous paper by Gormaz-Cuevas et al 5 The proposed model is based on the superstructure shown in Figure 2. As described in Gormaz- Cuevas et al, 5 the model consists of a set of mass balances in the treatment plant nodes, distribution and collection nodes, and consumption nodes.…”
Section: ■ Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…No one doubts the necessity of wastewater treatment due to its high amount of physical, chemical, and biological pollution which is only reachable through treatment plants. However, the high costs of these large-scale projects have led experts Citation: Gheibi to fi nd the most appropriate process that, besides meeting quality parameters, optimally satisfi es the technical, economic, and environmental goals [12][13][14][15][16]. On the other hand, each of these treatment plants and related processes has special characteristics and attitudes.…”
Section: Introductionmentioning
confidence: 99%